2010
DOI: 10.5539/jsd.v3n4p194
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to the Impact of Climatic Variations on Agriculture by Rural Farmers in North-Western Nigeria

Abstract: The impact of climatic variations on crop yields and the adaptation by farmers in north-western Nigeria are examined using the modeling approach and farm surveys. Accordingly, regression models which relate climate data to crop yields were constructed. The results showed that rainfall has a positive relationship with crop yields in the region and explained over 70 percent of the variations in the yields of sorghum, millet and maize, all of which were significant at the 0.05 level. Evaporation also had a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Some studies (e.g. Ajetomobi and Abiodun, ; Ekpoh, ) used statistical modelling techniques to investigate the relationship between crop yields and climate (rainfall and temperature) variability over the country. Ayanlade et al () applied Geographical Information System (GIS)/remote‐sensing approach to study the inter‐annual changes in (tuber) crops in response to rainfall and temperature variability between 1970 and 2000 over the Guinea Savanna ecological zone of Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies (e.g. Ajetomobi and Abiodun, ; Ekpoh, ) used statistical modelling techniques to investigate the relationship between crop yields and climate (rainfall and temperature) variability over the country. Ayanlade et al () applied Geographical Information System (GIS)/remote‐sensing approach to study the inter‐annual changes in (tuber) crops in response to rainfall and temperature variability between 1970 and 2000 over the Guinea Savanna ecological zone of Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Crop production, especially of maize, is faced with negative effects of extreme weather shocks believed to be corollaries of changing climate. According to Ekpoh, extreme weather shocks have direct effect on agricultural productivity [8]. McPhail et al, utilized extreme climate indicators to investigate the effect of climatic volatility on poverty, and concluded that extreme weather events are significant factors in defining food price movements [24].…”
Section: Introductionmentioning
confidence: 99%